1992
DOI: 10.1111/j.1365-2222.1992.tb00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and patient compliance of dust‐mite avoidance regimens in dwellings of mite‐allergic rhinitic patients

Abstract: We report on the mechanisms, the environmental changes and patient compliance with regard to conventional and new dust and mite avoidance measures to prevent allergic symptoms caused by mite allergens, taking into account both allergen contamination and the developmental success of pyroglyphid Acari. Twenty patients with persisting rhinitic complaints were selected and matched. Although the patients had performed some conventional dust and mite avoidance measures (patient compliance was 90%), the dwellings pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…An old study conducted with an acaricyde product reported that 50-90% of patients complied with the recommended avoidance measures [26]. An old study conducted with an acaricyde product reported that 50-90% of patients complied with the recommended avoidance measures [26].…”
Section: Allergen Avoidance Strategies and Pharmacotherapy For Allergmentioning
confidence: 99%
See 1 more Smart Citation
“…An old study conducted with an acaricyde product reported that 50-90% of patients complied with the recommended avoidance measures [26]. An old study conducted with an acaricyde product reported that 50-90% of patients complied with the recommended avoidance measures [26].…”
Section: Allergen Avoidance Strategies and Pharmacotherapy For Allergmentioning
confidence: 99%
“…There are very few data on the adherence of patients with dust mite avoidance measures (encasing mattresses and pillows, vacuum cleaning, removing carpets, and curtains etc.). An old study conducted with an acaricyde product reported that 50-90% of patients complied with the recommended avoidance measures [26]. On the other hand, a more recent study reported that only 35-50% of patients followed the recommendation of encasing pillows and mattresses [27], whereas the adherence to this measure was greater in a paediatric population, reaching a rate of 96% [28].…”
Section: Allergen Avoidance Strategies and Pharmacotherapy For Allergmentioning
confidence: 99%
“…1 The test may be a valid indicator of AD severity as a result of the relationship between immediate hypersensitivity responses and AD. It is also known as radioallergosorbent (RAST) testing, which is quantitative for all individual allergens.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, IgEQAA has been used by allergists in the diagnosis and treatment of diseases with known allergic triggers such as allergic rhinitis and asthma because of both IgEQAA's high sensitivity and specificity. 1 The test may be a valid indicator of AD severity as a result of the relationship between immediate hypersensitivity responses and AD. A review by Fuiano and Incorvaia details the specific mechanisms by which dust mite antigens aggravate the symptoms of AD.…”
Section: Introductionmentioning
confidence: 99%
“…A greater awareness of the aUergic basis of rhinitis for many sufferers has emphasized the Importance of allergen avoidance. For example house dust mite avoidance measures are of proven value In sensitive patients with both perennial rhinitis and asthma (2,3). The kientification of the major house dust mite allergens has enabled accurate measurement of allergen concentrations In dust samples, a pre-requlsite for developing new control measures Including barrier methods and acaricides.…”
mentioning
confidence: 99%